2018
DOI: 10.24926/iip.v9i4.1395
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy Internships: We Can Do Better

Abstract: The pharmacist’s role in patient care is expanding, and the profession must prepare its graduates for direct patient care. Internships can help facilitate this training outside of the formal pharmacy curriculum. Intern roles can expand beyond distributive tasks to compliment the full range of pharmacist activities, providing value to the student and institution. Crucially, outcomes measured must not only be traditional measures of student and pharmacist output, but also the growth and success of the student wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…4,5 However, previous research, which has been primarily descriptive in nature, has found that some intern programs focus mainly on hospital pharmacy operations and medication distribution, limiting the ability for student pharmacists to utilize their full potential. 6 Corresponding author: Chaeyeong Jang, PharmD Indiana University Health Methodist Hospital 1701 N Senate Ave, Indianapolis, IN 46202 Phone: 336-607-4893; Email: chaeyeong94@gmail.com In 2018, Nisly and Brennan called for action in this journal encouraging the profession to elevate the practice of pharmacy interns to allow for further development of clinical knowledge and critical thinking skills, as well as expand clinical services provided to patients. 6 In the same issue, they published a toolkit with suggestions on how to design, implement, and assess student internship programs.…”
Section: Description Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…4,5 However, previous research, which has been primarily descriptive in nature, has found that some intern programs focus mainly on hospital pharmacy operations and medication distribution, limiting the ability for student pharmacists to utilize their full potential. 6 Corresponding author: Chaeyeong Jang, PharmD Indiana University Health Methodist Hospital 1701 N Senate Ave, Indianapolis, IN 46202 Phone: 336-607-4893; Email: chaeyeong94@gmail.com In 2018, Nisly and Brennan called for action in this journal encouraging the profession to elevate the practice of pharmacy interns to allow for further development of clinical knowledge and critical thinking skills, as well as expand clinical services provided to patients. 6 In the same issue, they published a toolkit with suggestions on how to design, implement, and assess student internship programs.…”
Section: Description Of the Problemmentioning
confidence: 99%
“…6 Corresponding author: Chaeyeong Jang, PharmD Indiana University Health Methodist Hospital 1701 N Senate Ave, Indianapolis, IN 46202 Phone: 336-607-4893; Email: chaeyeong94@gmail.com In 2018, Nisly and Brennan called for action in this journal encouraging the profession to elevate the practice of pharmacy interns to allow for further development of clinical knowledge and critical thinking skills, as well as expand clinical services provided to patients. 6 In the same issue, they published a toolkit with suggestions on how to design, implement, and assess student internship programs. 7 The present study is in response to this call and designed with suggested concepts and innovations.…”
Section: Description Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation